KENDALA DALAM PENANGGULANGAN CYBERCRIME SEBAGAI SUATU TINDAK PIDANA KHUSUS - Agus Windara, I Made; Sukranatha, A A Ketut (Kertha Negara : Journal Ilmu Hukum, 2013)
As we know these days is rive veriety of crimes in both national and internationaldimensions that need special attention from law enforcement. One discussed the rampant crimeis cybercrime which can be done without knowing the limits of space and times so that thedistance also known as mayantara Crime. Cybercrime is one of the negative side effects of thedevelopment of increasingly sophisticated technology that prevention of these crimes requires anexpertise and specialized knowledge in the field of information technology.
Keywords: Information Technology, Cybercrime, Specific Crime